Novel Resorbable and Osteoconductive Calcium Silicophosphate Scaffold Induced Bone Formation - Ros-Tárraga, Patricia (Materials (Basel), 2016)
This aim of this research was to develop a novel ceramic scaffold to evaluate the response of bone after ceramic implantation in New Zealand (NZ) rabbits. Ceramics were prepared by the polymer replication method and inserted into NZ rabbits. Macroporous scaffolds with interconnected round-shaped pores (0.5–1.5 mm = were prepared). The scaffold acted as a physical support where cells with osteoblastic capability were found to migrate, develop processes, and newly immature and mature bone tissue colonized on the surface (initially) and in the material’s interior. The new ceramic induced about 62.18% ± 2.28% of new bone and almost complete degradation after six healing months. An elemental analysis showed that the gradual diffusion of Ca and Si ions from scaffolds into newly formed bone formed part of the biomaterial’s resorption process. Histological and radiological studies demonstrated that this porous ceramic scaffold showed biocompatibility and excellent osteointegration and osteoinductive capacity, with no interposition of fibrous tissue between the implanted material and the hematopoietic bone marrow interphase, nor any immune response after six months of implantation. No histological changes were observed in the various organs studied (para-aortic lymph nodes, liver, kidney and lung) as a result of degradation products being released.